2013
DOI: 10.1038/lsa.2013.20
|View full text |Cite
|
Sign up to set email alerts
|

Giant resonant light forces in microspherical photonics

Abstract: Resonant light pressure effects can open new degrees of freedom in optical manipulation with microparticles, but they have been traditionally considered as relatively subtle effects. Using a simplified two-dimensional model of surface electromagnetic waves evanescently coupled to whispering gallery modes (WGMs) in transparent circular cavities, we show that under resonant conditions the peaks of the optical forces can approach theoretical limits imposed by the momentum conservation law on totally absorbing par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 58 publications
5
54
1
Order By: Relevance
“…2(a), and coupled the fiber output to a photodiode connected to an oscilloscope. In a weak coupling regime, which is usually the case for polystyrene spheres in water, 22,37 the minimal values of transmitted signal can be achieved under contact conditions between the sphere and taper. Under these conditions, the intensity measured by photodiode can be used as a qualitative measure of the gap separating the microsphere from the taper.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…2(a), and coupled the fiber output to a photodiode connected to an oscilloscope. In a weak coupling regime, which is usually the case for polystyrene spheres in water, 22,37 the minimal values of transmitted signal can be achieved under contact conditions between the sphere and taper. Under these conditions, the intensity measured by photodiode can be used as a qualitative measure of the gap separating the microsphere from the taper.…”
Section: Resultsmentioning
confidence: 99%
“…Under resonant conditions (Δλ =0), we observed that the spheres tend to be optically attracted to the fiber. However, at very short separations the sphere is likely to be electrostatically repulsed from the fiber, 22 thus forming a potential minimum at a certain nanometer-scale distance from the taper required for stable propulsion. Once radially trapped, the resonant …”
Section: (D)mentioning
confidence: 99%
See 3 more Smart Citations